PEMETAAN ZONA RAWAN BENCANA KEKERINGAN UNTUK PENGEMBANGAN WISATA DI DESA WISATA NGLANGGERAN - Septiani, Astri Rahmawati; Azzahra, Yuzia Syaharani; Wijaya, Aurel Reynata; Manik, Yonatan Krisna; Saputro, Dimas Kurniawan; Pratama, Armandha Redo; Rahmafitria, Fitri (Universitas Pendidikan Ganesha, 2024)
This study aims to delineate drought hazard zones in Nglanggeran Tourism Village as a basis for disaster-aware tourism development. The area is characterized by high geotourism and cultural potential, yet is highly susceptible to drought due to its karst geomorphology and uneven rainfall distribution. A quantitative-descriptive approach was employed using Geographic Information Systems (GIS), incorporating spatial variables such as precipitation, soil type, land use, and slope gradient. Weighted overlay analysis was applied to generate a spatial zonation of drought vulnerability. The findings indicate that Nglanggeran is segmented into three zones: high vulnerability (24.8%), moderate (47.6%), and low (27.6%). These spatial patterns highlight the need for strategic planning that integrates environmental constraints and hazard risks. This study recommends incorporating geospatial data into local spatial planning (RTRW) and promoting educational and sustainable tourism initiatives that support water conservation and drought mitigation in hazard-prone zones.